Path Coefficient Analysis in Sugarcane - Chaudhary, R.R.; Chaudhary, N.K.; Sharma, R.C. (Journal of the Institute of Agriculture and Animal Science, 2003)
A study was conducted to estimate heritability of selected traits, and determine direct and indirect effects of selected plant traits on cane yield and sucrose content in sugarcane (Saccharum officinarum L.). Sixteen clones were evaluated in a replicated field experiment under irrigated conditions at Sugarcane Research Program, Jitpur, Nepal in 1999-2000. Eight morphological and three juice quality characters were studied. The 16 clone differed significantly for all the characters except juice purity. Broad sense heritability (hb2) estimates were high for stalk weight, stalk length, internode length, cane yield millable cane number, germination, and stalk diameter. Juice quality characters showed lower hb2 estimates. Cane yield showed significant positive correlations with stalk length, stalk weight, and internode number and length. Internode length was significantly positively correlated with brix and sucrose content in juice. The percent germination at 45 days after planting, and millable cane number were also important due to their positive direct effect on cane yield. Path coefficient analysis showed that stalk weight and length were the most important components of cane yield. The results suggest that stalk weight and length could be successfully used as indirect selection criteria to improve cane yield. J. Inst. Agric. Anim. Sci. 2003 24:13-19.